2019
DOI: 10.1111/ans.15414
|View full text |Cite
|
Sign up to set email alerts
|

Top 100 most frequently cited papers in liver cancer: a bibliometric analysis

Abstract: Background Bibliometric analysis has become popular in recent years, and increasingly more articles focusing on a particular disease are being published. The present study was performed to analyse the 100 most frequently cited papers in liver cancer (LC). Methods We searched the Thomson Reuters Web of Science database on 14 July 2018 to identify all potential manuscripts for this study. The search terms were ‘liver cancer’ and its synonyms. Manuscripts were listed in descending order by the total citations (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
1
11
0
2
Order By: Relevance
“…This prospective approach is frequently used, for example, to determine the most "successful" articles and authors in the various medical fields. Annually, various articles about "The 100 most cited manuscripts/articles" in specific medical field are published [77][78][79][80]. The data for these analyses can be easily obtained via bibliometric databases, such as Web of Science and Medline (PubMed), making this approach a quick and easy way to identify publications that are highly perceived by the scientific community.…”
Section: Comparison With Similar Trialsmentioning
confidence: 99%
“…This prospective approach is frequently used, for example, to determine the most "successful" articles and authors in the various medical fields. Annually, various articles about "The 100 most cited manuscripts/articles" in specific medical field are published [77][78][79][80]. The data for these analyses can be easily obtained via bibliometric databases, such as Web of Science and Medline (PubMed), making this approach a quick and easy way to identify publications that are highly perceived by the scientific community.…”
Section: Comparison With Similar Trialsmentioning
confidence: 99%
“…Jin et al have undertaken a bibliometric analysis of liver cancer in the current issue of ANZ Journal of Surgery. 5 Analysing the 100 most cited publications, they highlighted characteristics and the epidemiology of impactful papers. They demonstrated that an original idea is not a pre-requisite to be highly cited and that review articles can be highly cited and ranked in the top 10 articles in their field.…”
Section: Anzjsurgcommentioning
confidence: 99%
“…This prospective approach is frequently used, for example, to determine the most "successful" articles and authors in the various medical elds. Annually, various articles about "The 100 most cited manuscripts/articles" in speci c medical eld are published [77][78][79][80]. The data for these analyses can be easily obtained via bibliometric databases, such as Web of Science and Medline (PubMed), making this approach a quick and easy way to identify publications that are highly perceived by the scienti c community.…”
Section: Comparison With Similar Trialsmentioning
confidence: 99%